Supply Chain Management Issue : Development Science Techno Park (STP) Through Small, Medium Enterprises (SMEs), Case Study of Puspiptek Serpong Indonesia - Fadoli Fadoli; Sam’un Jaja Raharja; Margo Purnomo; Lina Auliana (International Journal of Supply Chain Management, 2019)
In the era of globalization where all industries must transform and make changes in order to survive sustainably, scientific studies are conducted to test how much influence innovation, Research & Development (R&D) and E-Commerce have on the performance of Small and Medium Enterprises (SMEs) at Puspitek Serpong in the perspective of Supply Chain Management (SCM). Grand Theory used in writing this article is